2021
DOI: 10.1038/s41598-021-87204-z
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing effect of quadruple multiple sequence alignments on deep learning based protein inter-residue distance prediction

Abstract: Protein 3D structure prediction has advanced significantly in recent years due to improving contact prediction accuracy. This improvement has been largely due to deep learning approaches that predict inter-residue contacts and, more recently, distances using multiple sequence alignments (MSAs). In this work we present AttentiveDist, a novel approach that uses different MSAs generated with different E-values in a single model to increase the co-evolutionary information provided to the model. To determine the im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…For structure modeling of individual proteins, the LZerD server uses AttentiveDist (Jain et al, 2021). If users have 3D structures of individual proteins to dock, they can skip the AttentiveDist step.…”
Section: Attentivedist Protein Structure Predictionmentioning
confidence: 99%
See 4 more Smart Citations
“…For structure modeling of individual proteins, the LZerD server uses AttentiveDist (Jain et al, 2021). If users have 3D structures of individual proteins to dock, they can skip the AttentiveDist step.…”
Section: Attentivedist Protein Structure Predictionmentioning
confidence: 99%
“…Although AttentiveDist was shown to have competitive performance at the time of the development (Jain et al, 2021), there are more recent methods that showed promising performance. Users are also encouraged to try such servers, perhaps those which performed well in recent CASP (Kryshtafovych et al, 2019).…”
Section: Attentivedist Protein Structure Predictionmentioning
confidence: 99%
See 3 more Smart Citations